Relations Between the Liturgy and Music in Religious System of Lithuanian Karaims - Firkavičiūtė, Karina (Acta Orientalia Vilnensia, 2000)
In this article a recent research on liturgy and music of Lithuanian Karaims (a Turkic nation confessing Karaism) is presented. The structural investigation of Karaim liturgy made for the first time allows the author to analyse the liturgical chant tradition as an active element of the liturgy and to clear out the relations between liturgy and music. The conclusion says, that there isn’t any systematic dependence between those two elements in Lithuanian Karaim liturgy, except: 1) the very narrow one – every kind of prayer has its own melody, and 2) the melody of a psalm to be chanted depends on either liturgical or non–liturgical occasion.